Give Me Liberty or Give Me . . . Alternatives?: Ending Cash Bail and Its Impact on Pretrial Incarceration - Sardar, Muhammad B. (2019)
Every day in the United States, thousands of pretrial defendants are imprisoned due to their inability to afford bail. These individuals have not been convicted of an offense, yet are incarcerated for the crime of being poor. Pretrial incarceration wreaks havoc both on the individual detainee and society at large. Pretrial detainees are more likely to plead guilty, receive higher sentences, and face grave future economic prospects. The cash bail system in particular disproportionately affects racial minorities, furthering the already racially disparate outcomes inherent in the U.S. criminal justice system. From a societal perspective, the increased rate of incarceration due to the inability to pay bail results in giant costs to a city or state’s budget. Catalyzed by these inequities, a third wave of bail reform is currently underway. Two particular alternatives to cash bail have been proposed and adopted by jurisdictions: risk assessment tools and electronic monitoring. Although these alternatives are steps in the right direction, both pose the risk of perpetuating the same problems associated with cash bail. Risk assessment tools can rely on racially biased data and have not yet been rigorously tested for empirical accuracy. Similarly, the use of electronic monitoring ignores the fundamental presumption of innocence by imposing onerous and punitive conditions on a pretrial detainee. Instead, this note advocates for state legislatures to use the success of community bail funds and the Washington, D.C. pretrial system as a building block to formulate legislation that: (1) releases pretrial misdemeanor detainees on personal recognizance; and (2) provides felony defendants with longer bail hearings and representation of counsel at these hearings